POTENSI WISATA KAMPOENG MATARAMAN TERHADAP EKONOMI MASYARAKAT LOKAL DESA PANGGUNGHARJO KECAMATAN BANTUL DAERAH ISTIMEWA YOGYAKARTA - Khairunnisa, Dena Abiyu; Mariya, Sri (JURNAL BUANA, 2024)
This study aims to determine the characteristics that exist in Kampoeng Mataraman village tourism. Knowing how important the role of involvement and the economy of the people of Panggungharjo Village is in the village tourism of Kampoeng Mataraman. The research method used was descriptive qualitative which was carried out by interviewing respondents and conducting direct research observations in the field by doing an internship for one week in Kampoeng Mataraman. After that, see how the economic life of the people of Panggunngharjo Village before and after working in Kampoeng Mataraman. The analysis technique is carried out using an interactive analysis model which requires three components in the form of data reduction, data presentation and drawing conclusions. The results of the research show that the most prominent characteristics of Kampoeng Mataraman are that they still show strong Javanese customs, a rural atmosphere, and typical Javanese joglo buildings. The impact of the development of Kampoeng Mataraman on empowering the people of Panggungharjo Village is that the community gains abilities that have so far been invisible from within themselves, increasing the economy of the people who work in Kampoeng Mataraman.